Pembuatan Biobriket dari Limbah Daun dan Batang Kayu Putih (Malaleuca leucadendron) Guna Memanfaatkan Limbah Hasil Pertanian di Kecamatan Jeruklegi Kabupaten Cilacap - Sonya Hakim Raharjo; Fatiha Nur Etnanta; Rosmawati Sipayung; Ebeng Sugondo; Asmaq Yuliah (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Oil reserves are increasingly decreasing in line with the use of non-renewable fossil fuels. One of the renewable energy sources is biomass. Some of the advantages of biomass briquettes are that they are environmentally friendly, more economical, and have better efficiency than coal briquettes. Eucalyptus leaves and stems (M. leucadendron) are the example of the biomass wastes that can be utilized as raw material for briquettes. The objectives of this research are to : Examine the fabrication of biobriquettes from the waste leaves and stems of eucalyptus (M. leucadendron); Examine the effect of the ratio of eucalyptus leaf and stem waste and adhesive on the characteristics of biobriquettes; Examine the effect of carbonization temperature of eucalyptus leaf and stem waste on the characteristics of biobriquettes; and Examine the effect of carbonization time of eucalyptus leaf and stem waste on the characteristics of biobriquettes. The biobriquettes fabrication process starts with the preparation of raw materials (drying), carbonization of biomass with a furnace, mixing raw materials with tapioca flour as adhesive, molding dough, and drying. Variable 6 with leaves and stems ratio is 5:1, with carbonization temperature of 800°C and carbonization time of an hour produces the best biobriquette product of water content 2.21 % and ash content 25.08%.